Training on Concept Mastery and Reasoning for the Academic Ability Test (TKA) Among Senior High School Students in Malang City - novie ary (Universitas Kristen Cipta Wacana, 2025)
The Academic Ability Test (TKA) is an essential instrument used in university admission processes, measuring students’ reasoning, numerical literacy, verbal comprehension, and conceptual mastery. However, many senior high school students in Malang City face significant difficulties in understanding reasoning-based question patterns, indicating the need for structured and intensive training. This community service activity aims to improve students’ abilities in solving TKA questions by emphasizing concept mastery and higher-order reasoning. The training included material explanation, guided problem-solving, practice exercises, simulations, and evaluations through pre-tests and post-tests. Results showed significant improvements, with a 28% increase in conceptual understanding, a 34% increase in reasoning skills, and 82% of participants reporting that the training helped them better understand TKA question patterns.